A Simplified Time-Domain Modulation Scheme-Based Maximum Boost Control for Three-Phase Quasi-Z Source Inverters - Sabeur, Nassereddine; Mekhilef, Saad; Masaoud, Ammar (Institute of Electrical and Electronics Engineers, 2018)
A new control method for the Z-source/quasi-Z-source inverter, also called the one dimension space-vector pulse width modulation (SVPWM) (OD-SVPWM)-based on the single-phase modulator technique to obtain maximum voltage gain is proposed in this paper. The attractiveness of the modulation method lies on its extreme simplicity. A simple mathematical model is necessary to develop the OD-SVPWM, and the calculations relative to switching sequence and the duty-cycles determination are highly simplified. Moreover, using a carefully selected shoot-through states the number of the switching transition is significantly decreased as each switch is locked to the positive or negative dc rail during a period of (2π/3). A simulation using MATLAB/Simulink and an experiment were carried out to demonstrate the validity and feasibility of the proposed control algorithm under different modulation index values.